A Novel Foraminoplasty Technique for Posterolateral Percutaneous Transforaminal Endoscopic Lumbar Surgery. Issue 1 (6th March 2020) - Liu, Xinchun; Peng, Yunfei
Abstract: BACKGROUND: In posterolateral percutaneous transforaminal endoscopic lumbar surgery, foraminoplasty is currently performed by resecting part of the superior articular process together with surrounding soft tissues. This procedure remains technically demanding. An ideal foraminoplasty technique should be safe, easy, efficient, and controllable and should minimize X-ray exposure. OBJECTIVE: To introduce a novel foraminoplasty technique that is designed in an attempt to obtain the ideal state. METHODS: The technique is introduced step by step by case illustration. Briefly, the technique is based on the addition of a novel instrument, named a "Foraminoplasty Working Tube, " to the commercialized spinal endoscope system. Through the foraminoplasty working tube, the foraminoplasty procedure can be performed under either reduced X-ray guidance or direct endoscopic view. RESULTS: The technique allows the surgeon to perform an accurate resection of the superior articular process by easily adjusting the foraminoplasty working tube to the target area. To a great extent, the volume of the bone resected is predictable and controllable and just meets the demands of the operation without excessive resection of the superior articular process. CONCLUSION: The present technique would potentially be a safer, easier, and more efficient foraminoplasty technique.